Analysis and soliton solutions of biofilm model by new extended direct algebraic method - Iqbal, Muhammad Sajid; İnç, Mustafa; Sohail, Saba; Khurshid, Hina; Chishti, Kalsoom (Vilnius Univ, Inst Mathematics & Informatics, 2023)
In this paper, the examination of soliton solutions of the biofilm model with the help of a new extended direct algebraic method is expressed. Besides the exact solutions, the existence of these solutions is also discussed with the help of the Schauder fixed point theorem. The nonlinear dynamical biofilm model which we consider in this paper is basically the bistable Allen-Cahn equation with quartic potential. For more physical understanding, the 3D plots of the solutions are presented. The different types of hyperbolic, trigonometric, and rational soliton solutions are gained. In the biofilm model, different parameters belong to certain spaces and give the exact solutions by applying the technique of new extended direct algebraic method. Exact solutions of the biofilm model are highlighted along with their restriction.
Keywords: biofilms model; existence of result; Schauder fixed point theorem; new extended direct algebraic method; soliton solutions